A review on community scale stationary and mobile production of biodiesel - Abduh, Muhammad Yusuf; Manurung, Robert; Heeres, Hero Jan; Mohamad Puad, Noor Illi (Institut Teknologi Bandung, 2021)
Biodiesel has been commercially produced on a large scale, but its application is still limited primarily due to its production cost, which is relatively more expensive than that of fossil fuel. Recently, there has been an ongoing parallel development whereby biodiesel production is carried out on a community scale, including a mobile production unit of biodiesel with local input and demand. The produced biodiesel is often intended for use by the concerned local community, which greatly reduces logistics and transportation cost. Unlike typical biodiesel production plants, a mobile biodiesel unit consists of a biodiesel production facility placed inside a standard cargo container and mounted on a truck, so that it can be transported to a region near the location of the raw materials. In this paper, we review existing concepts and units for the development of community-scale and mobile production of biodiesel. These include the main reactor technology for biodiesel production, as well as the pre-treatment prior to conveyance to the reaction unit and post-treatment. The pre-treatment includes oil extraction from oilseeds by an oil-expeller unit, as well as quality control of the oil before it enters the reaction unit. The post-treatment includes refining and purification of the biodiesel to meet the product specification set by the biodiesel industry. This paper also discusses the production cost of biodiesel on a community scale, particularly when using a mobile biodiesel unit. The production cost varies from $0.76-1.12/l. This range is still not yet competitive to the current average price of approximately $0.98/l of diesel around the world. The production cost may be reduced by applying a biorefinery concept that may translate into an economically alluring and environmentally attractive business model.